Augmented authenticity in athlete branding through human-AI co-production - Westerbeek, Hans (Frontiers in Sports and Active Living, 2025)
In the age of generative AI and digital self-production, athlete branding is undergoing a profound transformation. This conceptual paper introduces the idea of augmented authenticity to describe the co-creation of athlete identity through both human narrative and machine-generated content. Athletes today can operate as digital producers and autonomous entrepreneurs who increasingly rely on AI to scale engagement, personalise content, and deepen fan relationships. Drawing on literature from sport marketing, influencer culture, AI ethics, and digital platforms, this paper develops a scenario-based framework to explore how augmented authenticity may evolve. Three future scenarios, human-led branding with AI support, algorithmic co-production, and synthetic substitution, are used to stress-test strategic, ethical, and governance implications. The paper highlights how generative AI can empower underrepresented athletes while also creating new risks of losing control over the narrative and displacement of the athlete's identity. It argues that current sport governance models are ill-equipped for these shifts and proposes athlete-centred regulatory strategies to protect the control that athletes have over the narrative sovereignty, and their psychological well-being. Ultimately, the paper invites scholars, practitioners, and policymakers to engage with the future of athlete representation not merely as a technical challenge but as a philosophical question of what it means to be human in the platform age.